An Empirical Study of the Transnational Production Sharing of the Asian NICs with Japan - Kim, Ken I.; Kim, Kyoo H.; Lesage, James P. (Journal of International Business Studies, 1986)
The Purpose of the present study are: (1) to extend Kim and Kim's [1984] original study of transnational product sharing (TPS) of the Newly Industrializing Countries (NICs) of Asia with Japan from an aggregate-flow analysis to a product sectoral analysis; and (2) to provide additional empirical evidence for the macro economic approach to trade.